2021
DOI: 10.3390/biomedicines9121802
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte and Fibroblast Wound Healing In Vitro Is Repressed by Non-Optimal Conditions but the Reparative Potential Can Be Improved by Water-Filtered Infrared A

Abstract: It is a general goal to improve wound healing, especially of chronic wounds. As light therapy has gained increasing attention, the positive influence on healing progression of water-filtered infrared A (wIRA), a special form of thermal radiation, has been investigated and compared to the detrimental effects of UV-B irradiation on wound closure in vitro. Models of keratinocyte and fibroblast scratches help to elucidate effects on epithelial and dermal healing. This study further used the simulation of non-optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 122 publications
1
30
0
Order By: Relevance
“…19,20 It could recently be shown that wIRA radiation improved scratch healing under nonoptimal conditions in vitro. 25 In contrast, UV-B irradiation under the same conditions resulted in severe damage to keratinocytes as well as fibroblasts and wound healing was impeded. 25 Other light therapy devices might employ red light lasers (600-760 nm) at low intensity, e.g., 'low level laser light therapy' (LLLT), or light emitting diodes in the range of violet to green (380-495 nm), e.g., 'blue light phototherapy' and 'photodynamic therapy" (PDT).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 It could recently be shown that wIRA radiation improved scratch healing under nonoptimal conditions in vitro. 25 In contrast, UV-B irradiation under the same conditions resulted in severe damage to keratinocytes as well as fibroblasts and wound healing was impeded. 25 Other light therapy devices might employ red light lasers (600-760 nm) at low intensity, e.g., 'low level laser light therapy' (LLLT), or light emitting diodes in the range of violet to green (380-495 nm), e.g., 'blue light phototherapy' and 'photodynamic therapy" (PDT).…”
Section: Discussionmentioning
confidence: 99%
“…25 In contrast, UV-B irradiation under the same conditions resulted in severe damage to keratinocytes as well as fibroblasts and wound healing was impeded. 25 Other light therapy devices might employ red light lasers (600-760 nm) at low intensity, e.g., 'low level laser light therapy' (LLLT), or light emitting diodes in the range of violet to green (380-495 nm), e.g., 'blue light phototherapy' and 'photodynamic therapy" (PDT). Recently, positive effects of a novel, red-laser-based wound therapy device (WTD) on stimulation of cell regeneration and wound healing of connective tissue cells were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Human HaCaT cells (kindly provided by Prof. Norbert Fuesing, Heidelberg, Germany) and human primary keratinocytes (generated from juvenil phimosis; 4739-03/16) were cultured in 175 cm 2 cell culture flasks (Greiner bio-one, Frickenhausen, Germany) as previously described [ 68 ].…”
Section: Methodsmentioning
confidence: 99%
“…RNA purification, reverse transcription and real-time polymerase chain reaction were carried out as previously described [ 68 ]. Relative gene expression was calculated using the 2-ΔΔ Ct method using β-actin as a housekeeping gene for normalization [ 72 ].…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, several companies offer systems for the fully automated, high-throughput performance and analysis of wound scratch assays during large-scale screens ( Nowak-Sliwinska et al, 2018 ). This indicates that this type of assay is well-established and broadly used, not only to investigate the migratory activity of endothelial cells, but also of various other benign and malignant cell types ( Ideta et al, 2021 ; Wiegand et al, 2021 ; Fong et al, 2022 ).…”
Section: In Vitro Assaysmentioning
confidence: 99%